What are the characteristics of home exercise programs that older adults prefer?: A cross-sectional study - Simek, E.; Mcphate, L.; Hill, Keith; Finch, C.; Day, L.; Haines, T. (Lippincott Williams and Wilkins, 2015)
© 2015 Wolters Kluwer Health, Inc. Objective The aim of this study was to examine the preferences of older adults toward the structure and delivery of home exercise programs for the prevention of falls as well as the perceived benefits of and barriers to program adherence. Methods A two-wave cross-sectional telephone survey of community-dwelling older adults was conducted in Victoria, Australia. Respondents were categorized as current, previous, or nonparticipants of a home exercise program in the last 6 yrs. Thematic analysis of open-response questions examining the preferences of current and previous participants toward participation in, and delivery of, home exercise programs for falls preventions was performed. Results A total of 245 respondents completed the follow-up survey. The respondents were classified as current (n = 54), previous (n = 22), or nonparticipants (n = 169) of a home exercise program in the last 6 yrs. Program adherence was influenced by the perceived effect of programs on physical and mental health, participant autonomy, and how well the program structure complemented individual exercise and lifestyle preferences. Conclusions Adherence to home exercise programs for falls prevention is influenced by personal preferences toward program structure and delivery as well as perceived benefits of and barriers to program participation. To optimize participant adherence, service providers need to consider personal preferences and some flexibility in the program being delivered.